Socio-Economic Impact on the Sinamot Tradition from an Islamic Law Perspective (Analysis Study of Batak Tribe Customs in Padang Gelugur District, Pasaman Regency) - Nurul Hasanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Marriage is a fundamental social institution for humans, and almost all religious and cultural teachings regulate its implementation carefully. In Islam, marriage is not only seen from an essential perspective, namely to fulfill God's commands, but also from an ethical perspective, namely to respect and protect women's rights. One of the important elements in an Islamic wedding is the dowry, which serves as a sign of sincerity and respect for the bride. However, apart from religious teachings, cultural values and customs also play a significant role in people's lives. For example, in Padang Gelugur sub-district there is a